Analysis of the Effect of Shielding Gas Composition and FCAW Parameters on Shipbuilding Steel Plate for Ship Hull Production - Al Amin, Mochammad Karim; Soelistijono, Rafi Febian; Nisazarifa, Adristi; Ma'ruf, Buana; Nugroho, Priyambodo Nur Ardi; Mustaghfirin, Muhammad Anis; Putera, Erwien Yuliansyah; Irawan, Bambang; Anggara, Dika; Widodo, Eriek Wahyu Restu; Bachtiar, Bachtiar; Ibad, Ilham Khoirul; Pratama Putra, Mochammad Yudha Aditya (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2025)
Shielding gas is an important thing to protect the weld metal from impurities during the welding process. Ar, CO2, and mixing gas of Ar-CO2 are often used as a shielding gas in the marine industry. Differences in shielding gases and the current of welding could affect the microstructure and hardness of welding. This research analyzed the microstructure and hardness from the FCAW process of Shipbuilding Steel Plate using mixing gas and shielding gas of 100% CO2 with variations of current 180 and 195 A. The filler metal which has been used was A 5.20 E-71T1. The microstructure for the weld metal with 100% CO2 shielding gas was pearlite, widmanstatten ferrite, grain ferrite, and polygonal ferrite; otherwise for mixing shielding gas of 80% Ar + 20% CO2 and 75%Ar + 25% CO2 was found, the structure of pearlite, grain ferrite, and acicular ferrite. The effect of variations in the shielding gas composition and welding current that produced the highest hardness value was achieved with a shielding gas composition of 80% Ar + 20% CO2 and a current of 195 A, resulting in a hardness of 159.2 HV in the weld area.